O Hydroponic effluent as an alternative Fertilizer in Bell Pepper Production - Rios, Jhony Anderson Alvarenga; Ramirez, Daisy; Bernal Gini, Ernesto José; Rios Valiente, Lucia Simeona; da Silva, Glacy Jaqueline; Giombelli, Letícia Fernanda (Comunicata Scientiae, 2024)
As hydroponic systems expand and generate effluents, research has increasingly focused on their management due to potential environmental impacts. This study examined the effectiveness of using hydroponic effluents as fertilizer in bell pepper cultivation. The chemical composition of the effluents was analyzed and compared against water quality standards set by Resolution No. 222/02 of SEAM. The study employed two application methods (foliar and root) and three concentrations (0%, 50%, 100%) of effluents. A randomized complete block design was used to evaluate plant height, fruit number, and yield. Results showed that a 50% foliar application significantly increased plant height compared to the 100% concentration, with no significant differences in fruit number and yield. For root application, no significant differences were observed across the variables at different concentrations, although the best performance was noted at 50%. Comparative analysis between application methods revealed that root application resulted in taller plants but lower productivity. The study concludes that using hydroponic effluents as fertilizers affects bell pepper productivity, with a 50% concentration being most effective regardless of the application method.